Estimation of activity of air in the cyclotron bunker for PET diagnostics - Voskanjan Karen Varuzhanovich (Vestnik MGSU, 2012)
The paper presents the results of the estimation of air activation by argon-41 induced by accelerated protons in 18 MeV Cyclotron. It has been demonstrated that activity of air is below significant minimum at proton current of 150 microamps.